(untitled) (Malaysian Journal of Fundamental and Applied Sciences, 2017)
Marine clay is a soft soil that could be found widely at the coastal and offshore areas. This type of soil is usually associated with high settlement and instability, poor soil properties that are not suitable for engineering requirements and low unconfined compressive strength of less than 20 kPa. Considerable failure could occur even with light loads and it shows flat or featureless surface. This kind of soil is considered as problematic due to the existence of high moisture content and usually exists as slurry with noticeable percentage of expandable clay minerals. In this paper, the geotechnical, micro-structure and engineering properties of marine clay are thoroughly reviewed and discussed. The properties include moisture content, particle size distribution, specific gravity, Atterberg limits, mineral compositions and shear strength. Moreover, due to the increasing demand of construction at coastal and offshore areas involving the marine clay, many attempts have been made to stabilize this kind of soil in order to solve the geotechnical related problems. Some of the common stabilization methods used to improve the properties of marine clay such as cement grouting, chemical additives and some environmental friendly additives are discussed. In long term, marine clay treatment using cement was found to be the best method. In addition, this paper serves as a guideline for the design and construction of projects on marine soils.